Question and Answers Forum

All Questions      Topic List

Electric Current and Circuits Questions

Previous in All Question      Next in All Question      

Previous in Electric Current and Circuits      Next in Electric Current and Circuits      

Question Number 35496 by ajfour last updated on 19/May/18

Commented by ajfour last updated on 19/May/18

Solution to Q.35493

SolutiontoQ.35493

Answered by ajfour last updated on 19/May/18

(x+z)R+zR=yR= ξ      ...(i)  ⇒   xR+2zR=ξ  (q/C)=zR     ...(ii)  using (i) in (ii):  xR+((2q)/C) = ξ    and   as  x=(dq/dt)        (dq/dt) = (1/R)(ξ−((2q)/C))  ⇒    ∫_0 ^(  q)  (dq/(ξ−((2q)/C))) = ∫_0 ^(  t)  (dt/R)  ⇒    ln (ξ−((2q)/C))∣_0 ^q = ((−2t)/(RC))  or        ((ξ−((2q)/C))/ξ) = e^(−((2t)/(RC)))   ⇒    q = ((Cξ)/2)(1−e^(−((2t)/(RC))) ) .

(x+z)R+zR=yR=ξ...(i)xR+2zR=ξqC=zR...(ii)using(i)in(ii):xR+2qC=ξandasx=dqdtdqdt=1R(ξ2qC)0qdqξ2qC=0tdtRln(ξ2qC)0q=2tRCorξ2qCξ=e2tRCq=Cξ2(1e2tRC).

Terms of Service

Privacy Policy

Contact: info@tinkutara.com